CELEBRITY ENDORSEMENT AND PATRONAGE INTENTIONS OF POLITICAL PRODUCTS IN NIGERIAA LITERATURE REVIEW - Paschal Anayochukwu Ugwu (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
This paper aims at developing an integrative conceptual framework that explains the nexus between celebrity endorsement and patronage intentions of political products in a typical developing country context. Extant literatures reveal that there abounds literature on celebrity endorsement and patronage intentions but few studies have explained the nexus between Celebrity endorsement and patronage intentions of political products in a developing country like Nigeria. Also, the existing frameworks and models developed in advanced economies may not be suitable for developing street political product patronage behavior in Nigeria because of its peculiarities. The major importance of this study is to make available a comprehensive and robust framework for prospective researchers in this area, which will guide and direct their studies. The framework is premised on five key constructs- trustworthiness, expertise, attractiveness and congruency. More so, the proposed CELEBRITY ENDORSEMENT -PATRONAGE INTENTION conceptual framework is capable of providing insight for developing political marketing-related policies.